2010
DOI: 10.1002/pmic.201000376
|View full text |Cite
|
Sign up to set email alerts
|

2‐D DIGE analysis of the budding yeast pH 6–11 proteome in meiosis

Abstract: Meiosis is the cell division that generates haploid gametes from diploid precursors. To provide insight into the functional proteome of budding yeast during meiosis, a 2-D DIGE kinetic approach was used to study proteins in the pH 6-11 range. Nearly 600 protein spots were visualised and 79 spots exhibited statistically significant changes in abundance as cells progressed through meiosis. Expression changes of up to 41-fold were detected and protein sequence information was obtained for 48 spots. Single protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Targeted stage-specific proteolysis of cyclins and other proteins is already established as important for meiotic progression in S. pombe (Blanco et al, 2001;Funaya et al, 2012;Izawa et al, 2005;Kimata et al, 2008;Okuzaki et al, 2010;Pérez-Hidalgo et al, 2008). Furthermore, studies in Saccharomyces cerevisiae using 2D gels have revealed some changes in protein level during meiosis Scaife et al, 2010). We have shown in this study that Dma1p activity is required for the degradation of proteins at different stages of meiosis.…”
Section: Discussionsupporting
confidence: 50%
“…Targeted stage-specific proteolysis of cyclins and other proteins is already established as important for meiotic progression in S. pombe (Blanco et al, 2001;Funaya et al, 2012;Izawa et al, 2005;Kimata et al, 2008;Okuzaki et al, 2010;Pérez-Hidalgo et al, 2008). Furthermore, studies in Saccharomyces cerevisiae using 2D gels have revealed some changes in protein level during meiosis Scaife et al, 2010). We have shown in this study that Dma1p activity is required for the degradation of proteins at different stages of meiosis.…”
Section: Discussionsupporting
confidence: 50%
“…That study found that 142 protein spots were temporally regulated during meiosis but only identified 44 unique proteins by LC-MS/MS. 58,59 Here, TMT-based quantitative proteomics was applied to highly synchronized yeast cells at successive intervals following transfer to SPM, and 381 differentially expressed proteins (1.5-fold) of 2376 total identified proteins were found, significantly expanding our knowledge of meiosis at the proteome level. According to the studies of Chu et al and Primig et al, more than 1000 genes among approximately 6200 protein-encoding yeast genes showed significant changes (either induction or repression) in mRNA levels during sporulation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been seen in other studies-of the 50 proteins identified as being part of the yeast meiosis proteome, 30% are mitochondrial in function. 18,19 This is not surprising: in adult worms, the majority of cell growth and division, which are both energy-intensive processes, takes place in the germline. [20][21][22] Thus, the abundance of mitochondrial proteins in adult worms will correlate with the presence of a germline.…”
Section: Resultsmentioning
confidence: 99%